Designing Windows-Based Learning Applications Using Computer Network Material - Syahputra, Fahmy; Putri, Tansa Trisna Astono; Ramadani, Nadila; Al farishi, M Farid; Faturrahman, M Nadhif (CV. Rayyan Dwi Bharata, 2024)
This article discusses the design of a Windows-based learning application for computer network hardware. In the context of education, providing computer network hardware is often a challenge, especially in terms of understanding complex concepts. Therefore, interactive and interesting learning materials are needed to help students understand the material better. The application is designed using an interactive multimedia approach, combining text, images, animations, and videos to present information in a computer network. The design process includes needs analysis, user interface design, and development of program-related content. Application testing is carried out to ensure that the application meets learning objectives and can be used effectively by students. The results of the study show that this application not only improves students' understanding of computer networks but also provides a more enjoyable learning experience. Therefore, hopefully this learning application can be an effective tool in the teaching and learning process in educational environments.